Why did Inana Ascend from the Netherworld So Many Times? The Literary Growth of Inana’s Descent, 282-306 - Ayali-Darshan, Noga (Antiguo Oriente, 2023)
Lines 282-306 in the work Inana’s Descent to the Netherworld are the opening lines of the section situated between two literary units: the recounting of Inana’s journey to the netherworld and the recounting of Dumuzi’s descent to the netherworld. These lines are characterized by various textual differences, as well as multiple repetitions of the phrase “Inana ascended from the netherworld,” in both the temporal and indicative clauses. By examining each one of the repetitive phrases and its adjacent paragraph, the article traces the gradual development of that passage from one sentence into a paragraph of ca. 30 lines.